STRATEGI PENGUATAN JEJARING SOSIAL DI KAMPUNG LAMPION MALANG - Rahmawati, Intan; Anisa Putri, Yuna (Jurnal Bakti Masyarakat Indonesia, 2023)
The phenomenon of environmental pollution that is still rife is a form of lack of knowledge and public awareness to behave in love for the environment. One form of environmental pollution that still occurs is the act of throwing used cooking oil carelessly even though this trivial behavior can have a prolonged effect on the lives of living things. The service team had provided counseling about making laundry soap from used cooking oil in 2021 as an effort to reduce the act of throwing used cooking oil carelessly. The service team also urges the residents of Kampung Lampion to collect available used cooking oil to collectors, but the results are still minimal. This is the background for the service team to provide socialization related to the strategy of strengthening social networks which aims to increase the action of collecting used cooking oil in Kampung Lampion Malang and provide awareness of the importance of having a social network. The socialization was attended by eight women from RW 01 Kampung Lampion. This socialization will be held on May 29, 2022 at 08.00-11.00 WIB at the RW 01 Kampung Lampion Malang hall. The socialization activity began with an opening by the service team. Then participants were asked to fill out the pre-test sheet. Next, the speaker presented material about social networking. The socialization activity was ended by filling out the post-test sheet, evaluating the activities, and taking a group photo. The post-test results showed an increase in knowledge of community service participants in Kampung Lampion by 36.43% from the calculation of the difference between the pre-test and post-test scores. This is shown by residents who have begun to understand the existence of actors in strengthening social networks and how to build relationships with these actors through waste management cooperation. ABSTRAK: Fenomena pencemaran lingkungan yang masih marak terjadi merupakan bentuk kurangnya pengetahuan serta kesadaran masyarakat untuk berperilaku cinta lingkungan, Salah satu bentuk pencemaran lingkungan yang masih banyak terjadi adalah aksi membuang minyak jelantah secara sembarangan padahal perilaku sepele ini dapat menimbulkan efek berkepanjangan pada kehidupan makhluk hidup. Tim pengabdian sempat memberikan penyuluhan mengenai pembuatan sabun cuci dari minyak jelantah pada tahun 2021 sebagai upaya mengurangi aksi membuang minyak jelantah secara sembarangan. Tim pengabdian juga menghimbau warga Kampung Lampion untuk mengumpulkan minyak jelantah yang ada kepada pengepul namun hasilnya masih minim. Hal ini melatarbelakangi tim pengabdian untuk memberikan sosialisasi terkait strategi penguatan jejaring sosial yang bertujuan untuk meningkatkan aksi pengumpulan minyak jelantah di Kampung Lampion Malang dan memberikan kesadaran akan pentingnya dimilikinya jejaring sosial. Sosialisasi dihadiri oleh delapan orang ibu-ibu RW 01 Kampung Lampion. Sosialisasi ini dilakukan pada 29 Mei 2022 pukul 08.00-11.00 WIB di balai RW 01 Kampung Lampion Malang. Kegiatan sosialisasi diawali dengan pembukaan oleh tim pengabdian. Kemudian peserta diminta untuk mengisi lembar pre-test. Selanjutnya pemateri memaparkan materi mengenai jejaring sosial. Kegiatan sosialisasi di akhiri dengan pengisian lembar post-test, evaluasi kegiatan, dan sesi foto bersama. Hasil post-test menunjukkan terjadinya peningkatan pengetahuan pada peserta pengabdian masyarakat di Kampung Lampion sebesar 36,43% dari perhitungan selisih skor pre-test dan post-test. Hal ini ditunjukkan oleh para warga yang sudah mulai memahami adanya aktor-aktor dalam penguatan jejaring sosial serta cara dalam membangun hubungan dengan aktor tersebut melalui kerja sama pengelolaan limbah.